Pembelajaran Aktif Sebagai Pendekatan Pembelajaran Yang Inovatif - Zaeni Dahlan; Abrar Rayyan Sulthan; Eva Siti Faridah (STAI Al-Hamidiyah Jakarta, 2025)
Learning is a more specific part of education, namely the process of interaction between students and educators to acquire particular knowledge or skills. Learning that often focuses solely on the teacher and is delivered in a one-way manner is often ineffective, and the learning objectives are not achieved optimally. Students tend to become passive and less enthusiastic about learning. Based on this background, it is necessary to implement active learning that involves students directly, where the learning process centers on the students. This study is a literature review conducted using a descriptive qualitative approach. The data analyzed were obtained qualitatively, in the form of information sourced from various literature such as e-books, printed books, scientific journals, newspapers (both online and print versions), previous studies, articles, papers, reports, and magazines relevant to the topic. Active learning is an approach that places students at the center of the learning process by engaging them directly in it. Through participation in discussions, exploration, problem-solving, and reflection, this approach not only deepens conceptual understanding but also develops critical thinking, communication skills, and collaboration. Active learning with an innovative approach is a method that encourages student involvement through creative and need-based strategies. This method aims to create enjoyable, relevant, and meaningful learning experiences. Such an approach is highly appropriate to meet the demands of 21st-century education, which emphasizes the development of competencies, creativity, and independent learning.